Impact of the Probiotic on the Modulation of Vaginal Bacterial and Fungal Microbiota in HPV‐Positive Women - Pei, Xu; Mageswaran Uma, Mageswary; Azka Ainun, Nisaa; Shandra Devi, Balasubramaniam; Sarah, Samsudin; Nurul Izza, Mohamed Rusdi; Abigail Rembui, Jerip; Onn, Chern Ein; Mohamad Hafizi, Abu Bakar; Tan, Cheng Siang (Wiley-VCH GmbH, Weinheim, 2025)
This study examined the effects of administering the probiotic Lactiplantibacillus plantarum Probio87 on the vaginal microbiota of HPV-positive women, highlighting alterations in bacterial and fungal communities and their potential influence on vaginal and overall health. In a double-blind, randomized, placebo-controlled study, participants consumed daily doses of Probio87 (1 × 109 CFU/sachet) or a placebo for 12 weeks. Vaginal swabs were collected, and DNA was extracted for 16S rRNA and the internal transcribed spacer (ITS) region amplification via PCR, followed by sequencing of bacterial and fungal microbiota. The probiotic group showed improved alpha and beta diversity, with an increase in beneficial Lactobacillus (p = 0.014) and Phascolarctobacterium faecium (p = 0.041), while decreasing the abundance of pathogens like Streptococcus and Candida (p = 0.011). Additionally, vaginal health questionnaires linked probiotic use to improved vaginal and mental health in HPV-positive women. L. plantarum Probio87 demonstrated clinical and psychological benefits in HPV-positive women by balancing the vaginal microbiome, reducing pathogenic species, and promoting the growth of beneficial microorganisms.